Ultrasonic coupled abrasive jet polishing (UC-AJP) of glass-based micro-channel for micro-fluidic chip. (15th April 2023) - Ge, Jiangqin; Ren, Yile; Li, Chen; Li, Zhian; Yan, Sunting; Tang, Ping; Xu, Xinsheng; Wang, Qiang
Highlights: An ultrasonic coupled method is proposed for improving the efficiency of AJP. The polishing efficiency is effectively improved through the pulse effect. Periodic jet divergence does not affect the stability of material removal. There is an optimal amplitude range that can maximize the polishing efficiency. Abstract: The efficiency of abrasive jet polishing (AJP) is relatively low for glass-based micro-channels, and an ultrasonic coupled AJP (UC-AJP) approach was thus proposed. The fluid mechanic model of the UC-AJP was established to reveal the ultrasonic enhancement law and the optimal design parameters. The calculation results indicated that ultrasonic vibration could help significantly improve the turbulent kinetic energy and impact erosion that had an important role in jet stability and polishing efficiency. High-speed photograph and polishing experiments with different amplitudes were then performed to explore the performance of the proposed UC-AJP method. It was found that for glass-based micro-channel UC-AJP produced a smoother surface and higher polishing efficiency than AJP. There is an optimal amplitude range in the UC-AJP process, which can maximize the polishing efficiency for the micro-channel. Such improvements were ascribed to the synergistic effect of the pulse and cavitation as a result of the formation of pulsed abrasive jet. Graphical abstract: Image, graphical abstract